Value-Based Learning for SDGs: Integrating Bugis–Makassar Cultural Values (Siri’ Na Pacce) in Biology Education - Arifah Novia Arifin; Hardianto Hardianto; Oriny Tri Ananda (Universitas Muhammadiyah Palembang, 2026)
Biology education often emphasizes conceptual knowledge while overlooking the integration of values and real-life contexts, which are essential for sustainability-oriented learning. This study explored biology education students’ perceptions of the potential implementation of Value-Based Learning (VBL) through the integration of Bugis-Makassar cultural values, especially siri’ na pacce, in biology education. Using an exploratory qualitative design, data were collected from 26 students across undergraduate, master’s, and doctoral levels through an expert-validated open-ended questionnaire and analyzed by content analysis. The findings show that students perceive siri’ na pacce as a meaningful value-based content that aligns with biology concepts, particularly ecology and interdependence. Its integration was viewed as a bridge between abstract scientific concepts and students’ lived experiences, fostering contextual, meaningful, and sustainability-oriented learning. Students also reported increased engagement, conceptual understanding, ecological awareness, and social responsibility. However, challenges were identified, including limited teaching materials, lecturer readiness, and concerns about scientific objectivity. Overall, the study suggests that VBL grounded in local wisdom has strong potential to support character-based and SDGs-oriented biology education, provided that curriculum, pedagogical, and institutional support are strengthened.